Elementary differential equations and boundary value problems - Boyce, William E.; DiPrima, Richard C.; Boyce, William E. (New York, 1992)
In this Fifth Edition on the principal methods of solving differential equations, the authors take into account the easy availability of powerful calculators and personal computers. Discusses their use$1 (Bwith emphasis on geometrical interpretations and qualitative properties of solutions$1 (Band provides new problems which allow students to use computers in interesting and constructive ways. Also offers a variety of applications in both the physical and biological sciences.s
First Order Differential Equations. Second Order Linear Equations. Higher Order Linear Equations. Series Solutions of Second Order Linear Equations. The Laplace Transform. Systems of First Order Linear Equations. Numerical Methods. Nonlinear Differential Equations and Stability. Answers to Problems. Index.
Rev. ed. of: Elementary differential equations and boundary value problems, c1988.
Includes bibliographical references and index.
1
Keywords: Differential equations; Boundary value problems